Long latency reflexes in patients with postural instability and ataxia - Ersin Deneri (Neurological Sciences and Neurophysiology, 2020)
Objectives: Distal electrical stimulation of an upper extremity mixed nerve can generate a reflex response from the trapezius muscle. This reflex response may have a central neural pathway and can be affected by postural changes. Materials and Methods: In this study, long latency reflexes (LLRs) from both distal and trapezius muscle were evaluated in patients with Parkinson's disease (PD) with and without postural dysfunction and in patients with cerebellar ataxias. Thirty-three patients with PD, 10 patients with degenerative cerebellar ataxia and 22 healthy volunteers were included in the study. LLRs were recorded from ipsilateral thenar and trapezius muscles. Latencies and amplitudes of LLRs obtained from thenar (thenar LLR) and trapezius (trapezius LLR) muscles were analyzed. Results: In patients with PD, thenar LLRs showed significant shortening in the onset latencies and significant increase in the amplitudes in comparison with healthy controls. Trapezius LLRs did not show any significant difference in latencies or amplitudes; however, these responses showed a significant absence in one or two components in patients with Parkinson's disease with postural dysfunction. Additionally, this reflex was not recorded in patients with cerebellar ataxia. Conclusion: Trapezius LLRs can give some information regarding the physiology of neural circuits responsible for postural arrangement. Cerebellar connections may have a major role in the generation of trapezius LLRs.